2010
DOI: 10.1089/vbz.2009.0033
|View full text |Cite
|
Sign up to set email alerts
|

The TickIxodes pavlovskyias a Host of Spirochetes Pathogenic for Humans and Its Possible Role in the Epizootiology and Epidemiology of Borrelioses

Abstract: The tick Ixodes pavlovskyi is taxonomically, morphologically, and ecologically close to the taiga tick Ixodes persulcatus, a major host and vector of Borrelia spirochetes. The recent range of I. pavlovskyi is disjoined into the Western Siberian and Far Eastern parts, with this tick being almost always sympatric with I. persulcatus. A total of 56 unfed adult I. pavlovskyi ticks from the biotope where this species was absolutely dominant (within the city limits of Tomsk, Western Siberia) and 50 I. persulcatus ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The reason remains unclear, but the inhabitant species of ticks may be associated with this geographical difference. Furthermore, Korenberg et al recently found that I. pavlovskyi and I. persulcatus ticks differ in their abilities to transmit borrelia (12). This finding may support the notion that the resident tick species contributes to the determination of the endemic species B. garinii.…”
mentioning
confidence: 73%
“…The reason remains unclear, but the inhabitant species of ticks may be associated with this geographical difference. Furthermore, Korenberg et al recently found that I. pavlovskyi and I. persulcatus ticks differ in their abilities to transmit borrelia (12). This finding may support the notion that the resident tick species contributes to the determination of the endemic species B. garinii.…”
mentioning
confidence: 73%
“…Indeed, several human pathogens have been detected in this tick species [36, 48, 51, 66, 67]; however, thorough investigations of the ability of I. pavlovskyi ticks to transmit a wide range of pathogens have not been conducted. In this study, the prevalence and genetic diversity of TBEV, KEMV, B. burgdorferi ( s.l .…”
Section: Discussionmentioning
confidence: 99%
“…The cause of the recent expansion of I. pavlovskyi ticks is unknown. Limited data have been reported on the detection of tick-borne pathogens in these ticks, including TBEV, KEMV, B. afzelii , B. garinii and B. miyamotoi [36, 43, 48, 51, 66, 67]. In addition, DNA of A. phagocytophilum and “ Ca.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, I. pavlovsky i can serve as an additional vector for B. miyamotoi . I. persulcatus and I. pavlovskyi are closely related morphologically, ecologically and phylogenetically [17], [28]. The larvae and nymphs of both tick species have a wide range of feeding hosts, such as small mammals and birds.…”
Section: Discussionmentioning
confidence: 99%